Пусть х-2=а; у+3=b, тогда
3а²+7b³=5
2a²-7b³=15
5a²=20
2a²-7b³=15
a=2; -2
a=2
b= -1
a= -2
b= -1
возвращаемся к замене
х-2=2. х-2= -2
у+3= -1. у+3= -1
х=4. х=0
у= -4. у= -4
1) 6:3/11=6*11/3=22 км/ч скорость велосипедиста
2) 6+22=28 км/ч скорость сбтжения
1кг-560г=,,,,,,1ц-76кг=,,,,8грн-560к=,,,,3м-109см=,,,,,8дм-45см=,,,
nani179767
1)440г
2)24кг
3)240к
4)191см
5)35см
1. 3 м. 47 см - 19 дм = 34,7-19=15,7дм=1,57м
<span>2. 316 кг + 4 ц=3,16+4=7,16ц=716кг</span>
1)83,2+2,66=85,86 2)пацан у тебя ничего не получится я честно говорю